The Influence of Work Motivation, Work Discipline and Workload on Employee Performance at PT Sanwa Engineering Batam - Oguna’ O Harefa; Asron Saputra (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
To determine the success of an organization, the most important thing is the existence of employees who are capable and skilled, and have high morale so that employee performance can produce good output. One thing that needs to be considered by the company towards its employees is work motivation, work discipline and workload. Therefore this study aims to determine the extent to which work motivation, work discipline and workload affect employee performance. Which this research will be conducted at PT Sanwa Engineering by distributing questionnaires to employees. This type of research is quantitative research. The sample used in this study was 193 respondents using the non-probability sampling technique. The data analysis technique used is multiple linear regression. The results of multiple linear regression show that work motivation has a positive and significant effect on employee performance with a t count of 4.791 > t table of 1.973. The work discipline variable has a positive and significant effect on employee performance with a t value of 6.208> a t table value of 1.973. The workload variable has a positive and significant influence on employee performance with a t count of 4.818> t table of 1.9726.